The A.B.C. murders : a Hercule Poirot novel - Christie, Agatha, 1890-1976. (New York : Black Dog & Leventhal Publishers : Distributed by Workman Pub. Co., 2006)
A is for Ascher, cudgeled in Andover. B is for Barnard, strangled in Bexhill. C is for Clarke, struck down in Churston. Beside each body is an A.B.C. Railway guide; before each murder Hercule Poirot is notified. In one of Christie's most twisted tales, the meticulous Belgian sleuth must navigate the eerie maze of a serial killer's mind. D is for Doncaster, where the next victim dies... E is for evidence, ingeniously analyzed.
The letter -- Andover -- Mrs. Ascher -- Mary Drower -- The scene of the crime -- Mr. Partridge and Mr. Riddell -- The second letter -- The Bexhill-on-sea murder -- The Barnards -- Megan Barnard -- Donald Fraser -- A conference -- The third letter -- Sir Carmichael Clarke -- Marking time -- Poirot makes a speech -- By way of Sweden -- Lady Clarke -- Description of a murderer -- September 11th, Doncaster -- The Doncaster murder -- At Scotland yard -- Hercule Poirot asks questions -- And catch a fox -- Alexander Bonaparte Cust -- Poirot explains.
"Published by arrangement with G.P. Putnam's Sons, a member of Penguin Group (USA) Inc."--T.p. verso.
Keywords: Poirot, Hercule -- (Fictitious character) -- Fiction; Private investigators -- England -- Fiction; Belgians -- England -- Fiction; Mystery fiction